1990
DOI: 10.1002/ppul.1950090305
|View full text |Cite
|
Sign up to set email alerts
|

Effects of chest physical therapy on lung function in children recovering from acute severe asthma

Abstract: The effects of chest physical therapy in acute severe asthma in children have been studied in 38 children aged 6 to 13 years in a randomized placebo controlled trial. The study began between 6 and 24 hours after admission to hospital; 19 children received chest physical therapy (PT) and 19 children received placebo visits. Each child had 4 treatments over 2 days which were preceded by nebulized salbutamol. Lung volumes and flow rates were measured in a body plethysmograph before salbutamol and before and after… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
48
0
2

Year Published

2000
2000
2013
2013

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(50 citation statements)
references
References 9 publications
0
48
0
2
Order By: Relevance
“…24 CPT included relaxation techniques (positioning, lateral costal or diaphragmatic breathing, shoulder relaxation), secretion clearance techniques (postural drainage, coughing, forced expiratory technique, vibration, wing flapping), thoracic mobility exercises, and postural correction exercises.…”
Section: Studies Evaluating Cpt In Non-postoperative Subjectsmentioning
confidence: 99%
See 3 more Smart Citations
“…24 CPT included relaxation techniques (positioning, lateral costal or diaphragmatic breathing, shoulder relaxation), secretion clearance techniques (postural drainage, coughing, forced expiratory technique, vibration, wing flapping), thoracic mobility exercises, and postural correction exercises.…”
Section: Studies Evaluating Cpt In Non-postoperative Subjectsmentioning
confidence: 99%
“…14,17,19,24,25,29,32,34,37,40,42,43,44 Three studies reported improved results: a poor quality study of IPV ϩ CPT versus CPT in ICU subjects, with COPD reported better pulmonary function tests in the intervention group 18 ; and a poor quality study of spirometry plus Deep breathing exercises, sustained maximal inspiration, postural drainage, manual percussion Ambrosino 32 …”
Section: Pulmonary Function Testsmentioning
confidence: 99%
See 2 more Smart Citations
“…The concern would be that you could increase oxygen demand and also stress a patient who is already stressed. 88 How then, do we deal with secretion clearance in patients with acute asthma? Some support the cough and respiratory effort or drive by utilizing noninvasive ventilation to limit fatigue, whereas others utilize PEP therapy to prevent distal airway collapse.…”
Section: Asthmamentioning
confidence: 99%